2015
DOI: 10.1155/2015/230297
|View full text |Cite
|
Sign up to set email alerts
|

Er:YAG Laser Assisted Treatment of Central Odontogenic Fibroma of the Mandible

Abstract: Central odontogenic fibroma is a very rare benign odontogenic tumour characterized by a fibrous mature stroma with variable strands or islands of inactive-looking odontogenic epithelium. Our aim is to report a case of a central odontogenic fibroma and describe the clinical usefulness of Er:YAG laser for the surgical treatment of this tumour. A 74-year-old woman presented with an expansive lesion located in a mandible with multilocular and mixed radiographic appearance. A conservative excision using Er:YAG lase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Peripheral odontogenic fibroma presents as a gingival mass, resembling fibrous hyperplasia. The peripheral type occurs twice as often in females than males and the incidence peak is between second to fourth decades of life ( 32 , 33 ).…”
Section: Odontogenic Benign Tumors Mesenchymalmentioning
confidence: 99%
See 1 more Smart Citation
“…Peripheral odontogenic fibroma presents as a gingival mass, resembling fibrous hyperplasia. The peripheral type occurs twice as often in females than males and the incidence peak is between second to fourth decades of life ( 32 , 33 ).…”
Section: Odontogenic Benign Tumors Mesenchymalmentioning
confidence: 99%
“…Recurrence is rare. It has been reported that recurrence occurs due to insufficient removal of the lesion ( 32 , 33 )…”
Section: Odontogenic Benign Tumors Mesenchymalmentioning
confidence: 99%
“…(5,23) Odontogenic fibroma is a rare OT, relatively common in females and the incidence peak is between second to fourth decades of life. (52,53) In this study, odontogenic fibroma constituted 7.69% of OTs, no sex predilection, equal occurence in maxilla and mandible were observed. These contradicted studies referring to the common occurrence in females.…”
Section: Discussionmentioning
confidence: 46%
“…The histological subtype of COF was indeterminate in 37% of cases. Otherwise the distribution between the complex type and the simple type appeared to be almost equivalent with 34.1% of cases [8,15,21,23,26,[28][29][30][34][35][36][37]39,40,46,47,[50][51][52][53][54]56,57,60,61,63,65,[70][71][72][73][74]76,78,80,82,85] and 28.9% of cases respectively [6,7,[11][12][13][14]17,18,20,22,24,25,27,31,…”
Section: Histological Featuresmentioning
confidence: 99%